Community's Vulnerability to Drought-Driven Water Scarcity and Food Insecurity in Central and Northern Semi-arid Areas of Tanzania - Mdemu, Makarius V. (Frontiers in Climate, 2021)
Droughts are one of the most serious threats to water availability, food security, and local livelihoods in the semi-arid areas of Tanzania. This paper adapted the participatory vulnerability assessment tools (causal effects, social mapping–resource mapping–social services–mobility–seasonality) to analyze the effects of prolonged droughts on semi-arid farming systems, community's vulnerability to drought effects, and the adopted coping strategies in six villages of Chamwino and Mwanga districts. Crop failure, loss of pasture, and drying of water sources were the common and major negative effects of droughts. Their consequences included food shortage and insecurity, water scarcity, and loss of livestock. The vulnerability to these effects was found to be driven by the social condition of households, resource ownership, and type of income sources. Those with good social conditions, relatively resourceful and deriving incomes from crop-livestock integration or non-agriculture, were less vulnerable and better placed to cope with the effects of droughts. Investments that build the productive resource base of a household and improve access to domestic and livestock water will contribute to long-term adaptive and drought-resilient systems in semi-arid areas of Tanzania.